Silent Political Apathy in Urban Society: The Case of Medan 2018 Election - Derajad Sulistyo Widhyharto; Desi Rahmawati; Norin Mustika Rahadiri Abheseka (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Studies on non-voting behavior and which depart from social perspectives have long been stagnated due to the dominance of analysis that puts systems, institutionalization, political mechanisms and participation as the main viewpoints of the studies. This study using social perspectives is useful to explain why voters were not present at polling stations during the Medan 2018 Election. It elaborates the social aspects that influenced non-voting behavior in the urban area of Medan in North Sumatra, Indonesia during the 2018 gubernatorial election. Utilizing mix- method strategies, instead of citing social aspects as a mere research context, this article argues that social aspects in the form of social cleavages worked behind the silent apathy, namely apathy that was implicitly indicated by voters who were not present at polling stations. Social cleavages including ethnicity, religion and gender indicated a paradox since they—with the exception of gender—were used by candidates as the main campaign substance. On the other hand, large numbers of people showed disinterest in these social cleavages during the election. This article explains why abstained voters hid their disinterest behind their excuses for not being present at the polling stations for economic (working activities) and other reasons.